Ladybug Girl and Bingo - Soman, David; Davis, Jacky, 1966- (New York : Dial Books for Young Readers, 2012)
Lulu, who likes to dress in a ladybug costume, goes camping with her parents, brother, and dog Bingo.
Keywords: Camping -- Juvenile fiction; Dogs -- Juvenile fiction; Fiction; Fiction; Picture Book